Effect of feeding management on the nutritional composition of Mexican artisan soft cheese made with raw or pasteurized goats’ milk - PUGA, D C; GALINA, H M; BONILLA, C A; CUCHILLO, H M; MONTAÑO, B S; CASTILLO, D R; VILLAREAL, E; PÉREZ-GIL, R F (The Indian Journal of Animal Sciences, 2011)
A study was conducted to evaluate the effect of grazing on the nutritional composition of artisan soft goat cheese. Groups A and B were formed. Group A was managed with supplementation on goats grazing in the semiarid rangeland. Group B goats were kept full indoors fed with lucerne hay and grain concentrate. Results indicated that feeding system and heat treatment did not affect the major composition (protein, ash, energy, fat and cholesterol) of the cheese. Polyunsaturated acids had higher concentration in indoor than grazed cheese. Indoor cheeses were slightly better than the product of grazing goats, probably due to the effect of dry winter on the quality and quantity of forages consumed.